PENGARUH VOLUME CAIRAN RUMEN SAPI TERHADAP BERMACAM FESES DALAM MENGHASILKAN BIOGAS - Wati, Linda; Ahda, Yuni; Handayani, Dezi (IAIN Batusangkar, 2014)
This research is aimed at investigating the influence of cow?s rumen fluid volume toward varied feces in producing biogas. This research has been done since October to December 2013 at Biotechnology laboratory, Faculty and Mathematic Science. The method of this research was completely randomized design (CRD) with factorial in three times. The first factor as the treatment was the type of feces, such as cow, horse, goat, and buffalo?s feces. The second factor was the treatment by adding the volume of cow?s rumen liquid as many as 160 and 320 ml. The control was the treatment without adding the volume of cow?s rumen liquid. The variables that were measured in this research were the volume of biogas and the duration of biogas flame that could be produced. The result of this research shows that the type of feces affected the biogas production. In these treatments, the highest volume of biogas that was produced to the lowest were horse?s feces yield of 226.56 cm3, cow?s feces yield of 71.40 cm3, buffalo?s feces yield of 28.28 cm3, and goat?s feces yield of 2.13 cm3. The addition of rumen liquid can increase the biogas production on cow, goat, and buffalo?s feces, but it did not significantly give the effect on horse?s feces. The positive interaction between addition of rumen liquid and feces shows on cow, goat, and buffalo?s feces. The rumen liquid, however, was not interacted with horse?s feces for producing biogas.Key words: biogas, rumen fluid, methanogen